2021
DOI: 10.32479/ijeep.10735
|View full text |Cite
|
Sign up to set email alerts
|

Are Urban Rwandan Households Using Modern Energy Sources? An Exploration of Cooking Fuel Choices

Abstract: This study employed a discrete choice framework to explore cooking energy use patterns amongst urban Rwandan households using the latest EICV 5 microeconomic survey dataset. Specific analysis focused on choices for three primary cooking fuels namely: firewood, charcoal and liquidified petroleum gas. The findings show that ordered model provided better prediction for primary fuel choices rather than the secondary choices for multiple fuel users with income as a key determinant. Furthermore, asset index, house o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…These include regional gaps in terms of access to new modern energy services such as LPG ( Chapman and Okushima, 2019 ). For instance, an exploratory study on cooking fuel choices in urban Rwanda found that fuelwood still dominates in poor households, while charcoal as a transitional fuel remains the most dominant primary cooking fuel not only for the middle class but also for the richest households ( Khundi-Mkomba, 2021 ). Regarding policy implications, the paper also discussed the need to promote an all-inclusive approach.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These include regional gaps in terms of access to new modern energy services such as LPG ( Chapman and Okushima, 2019 ). For instance, an exploratory study on cooking fuel choices in urban Rwanda found that fuelwood still dominates in poor households, while charcoal as a transitional fuel remains the most dominant primary cooking fuel not only for the middle class but also for the richest households ( Khundi-Mkomba, 2021 ). Regarding policy implications, the paper also discussed the need to promote an all-inclusive approach.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Like other previous EICVs, the EICV5 (2016/17) has been used in various academic studies and research projects (Diao et al 2021;Khundi-Mkomba 2021;Maniriho et al 2020: 21-41;Muremyi et al 2019;Nsabimana et al 2021Nsabimana et al , 2022. For instance, Maniriho et al (2020) use EICV5 to evaluate rural household savings and their implications on welfare in Rwanda.…”
Section: Previous Analysis Of the Datamentioning
confidence: 99%